2017
DOI: 10.1016/j.alit.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Japanese guidelines for food allergy 2017

Abstract: Five years have passed since the Japanese Pediatric Guideline for Food Allergy (JPGFA) was first revised in 2011 from its original version. As many scientific papers related to food allergy have been published during the last 5 years, the second major revision of the JPGFA was carried out in 2016. In this guideline, food allergies are generally classified into four clinical types: (1) neonatal and infantile gastrointestinal allergy, (2) infantile atopic dermatitis associated with food allergy, (3) immediate-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
208
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(220 citation statements)
references
References 72 publications
1
208
0
1
Order By: Relevance
“…Wheat allergy is the third most common food allergy that develops during infancy in Japan [10, 11]. Although research groups such as Keet et al [12] and Czaja-Bulsa et al [13] have previously reported on the wheat allergy history exhibited by patients in Western populations, the topic has been poorly studied in Asian (including Japanese) populations.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat allergy is the third most common food allergy that develops during infancy in Japan [10, 11]. Although research groups such as Keet et al [12] and Czaja-Bulsa et al [13] have previously reported on the wheat allergy history exhibited by patients in Western populations, the topic has been poorly studied in Asian (including Japanese) populations.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments for provoked reaction were based on the European Academy of Allergy and Clinical Immunology's food allergy and anaphylaxis guidelines [9]. Anaphylaxis was defined according to World Allergy Organization Anaphylaxis Guidelines [10], and severity of symptoms was defined according to Japanese anaphylaxis guidelines [8,11].…”
Section: Oral Food Challengementioning
confidence: 99%
“…In total, 64 g of BW noodles containing 3,072 mg of BW protein were used for OFC as previously described [4] (based on the 2017 Japanese Pediatric Guidelines for Food Allergy [8]). Treatments for provoked reaction were based on the European Academy of Allergy and Clinical Immunology's food allergy and anaphylaxis guidelines [9].…”
Section: Oral Food Challengementioning
confidence: 99%
“…При этом следует учитывать, что частота аллергиче-ских заболеваний варьирует в зависимости от воз-раста пациентов. Распространенность пищевой ал-лергии оценивается в 5-10 % у младенцев, 3-5 % -у детей младшего возраста и 4,5 % -у школьников [2]. У маленьких детей наиболее частой локализацией аллергического процесса является пищеваритель-ный тракт (например, пищевая аллергия), что кли-нически проявляется симптомами поражения кожи и слизистых оболочек.…”
Section: резюме в статье представлен обзор литературы о современных unclassified